1994
DOI: 10.1080/01690969408402108
|View full text |Cite
|
Sign up to set email alerts
|

Are children's representations of words distributed? effects of orthographic neighbourhood size, consistency and regularity of naming

Abstract: Two groups of-children with mean ages of 7.47 and 9.04 years and with reading ages of 7.27 and 9.48 years respectively were asked to read lowfrequency words which differed in the consistency and regularity of their endings and which had many or few orthographic neighbours. Both groups found words with many neighbours easier to read than those with few. Only the better readers were affected by the type of ending; regular-consistent words were easier than both regular-inconsistent words and exception words which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
30
2
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 34 publications
16
30
2
3
Order By: Relevance
“…The experiment successfully repeated the well-established facilitatory N effects for lexical decision for centrally presented words (Laxon et al, 1988(Laxon et al, , 1994. Experiment 2 investigated whether VHF and length would interact once N was controlled.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The experiment successfully repeated the well-established facilitatory N effects for lexical decision for centrally presented words (Laxon et al, 1988(Laxon et al, , 1994. Experiment 2 investigated whether VHF and length would interact once N was controlled.…”
Section: Discussionmentioning
confidence: 84%
“…Orthographic neighborhood size (''N'') is defined as the number of words differing from a target word by one letter (i.e., ''neighbors'') (Coltheart, Davelaar, Jonasson, & Besner, 1977). Previous studies have shown, in general, facilitation effects in lexical decision for words with larger N's (''friendly'' words) (Laxon, Coltheart, & Keating, 1988;Laxon, Masterson, & Moran, 1994). N effects are robust when frequency, regularity, and age of acquisition are controlled, though frequency of the neighboring words may interact with N (Perea & Pollatsek, 1998;Segui & Grainger, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…2 In addition to the infralexical characteristics of words, several studies indicate that reading performance is affected by the density of a word's lexical neighborhood, which corresponds to the number of orthographically similar words. Laxon and colleagues (Laxon, Coltheart, & Keating, 1988;Laxon, Masterson, & Moran, 1994) showed that words that are orthographically similar to many other words are read better by children. A similar effect has been observed for French-speaking adults reading words that were GPC-consistent (Dubois-Dunilac, Peereman, & Content, in preparation;Peereman & Content, 1995.…”
Section: Main Variables In the Study Of Literacy Acquisition: A Shortmentioning
confidence: 99%
“…The strategy may be: If I don't know a word I'm going to guess the most common real word that has the same initial sound(s). These miscues may also be explained through the frequency of orthographic triples (Seidenberg & McClelland, 1989;Laxon et al, 1994) in that che_ is more commonly followed by e than s, and dre is more common than des. Whatever the theoretical interpretation of these miscues, they are very similar to those reported by Laxon et al (1988;.…”
Section: A Qualitative Look At Miscuesmentioning
confidence: 99%
“…The percentages of miscues on low-frequency words and nonwords read from lists were calculated based on each reader's correct reading of the rime in the matching highfrequency target word. These miscues were then placed into three categories depending on which part of the target word or nonword was preserved in the miscue: (a) rime-match miscues were defined as incidents when readers maintained the rime portion when misreading the low-frequency word or nonword; (b) scaffolded miscues (Laxon et al, 1994) were defined as miscues that maintained the initial and final sounds of the target word or nonword; and, (c) single-phoneme miscues were defined as miscues that preserved one phoneme of the target word or nonword. The percentage of miscues on low-frequency words and nonwords attempted in lists can be seen in Table 2.…”
Section: Miscue Analysis Of Low-frequency Words and Nonwords Read In mentioning
confidence: 99%